Possibility of Hg redistribution in tridax procumbens due to Hg contamnination. - Chew, W.; Yap, Chee Kong; Ismail, Ahmad; Zakaria, Mohamad Pauzi; Tan, Soon Guan (EM International, 2011)
This study was conducted to determine the possibility of Hg redistribution in Tridax procumbens due to Hg contamination in Peninsular Malaysia. In the present study, the overall ranges of Hg were found to be 1.59 μg/kg - 12.7 μg/kg for flowers, 1.76 μg/kg - 9.33 μg/kg for stalks, 10.6 μg/kg - 57.8 μg/kg for leaves, 1.95 μg/kg - 6.14 μg/kg for stems and 2.86 μg/kg - 32.5 μg/kg for roots. Evidence of Hg redistribution found in T. procumbens that were sampled from two sites (Bandar Baru Bangi-2 and Kg. Sg. Ahceh) where Hg concentration in the soil were also high. At both sites, roots of T. procumbens displayed higher concentrations of Hg when compared with leaves. This which was different from the results of the other sites. Therefore, Hg redistribution could be used as an indicator of Hg contamination. However, further studies are needed to confirm this possibility.